Extrusion of flavored corn grits: Structural characteristics, volatile compounds retention and sensory acceptability - Menis, Michele Eliza Cortazzo [UNESP]; Milani, Talita Maira Goss [UNESP]; Jordano, Amanda [UNESP]; Boscolo, Maurício [UNESP]; Conti-Silva, Ana Carolina [UNESP] (Elsevier, 2013)
The effects of the moisture content of the raw material, extrusion temperature and screw speed on flavor retention, sensory acceptability and structure of corn grits extrudates flavored with isovaleraldehyde, ethyl butyrate and butyric acid were investigated. Higher temperature resulted in more expanded extrudates with lower density and cutting force, while higher moisture content increased ethyl butyrate retention. The most acceptable extrudates were those obtained with low moisture content, under conditions of high extrusion temperature and high screw speed, or low screw speed and low extrusion temperature, whereas the aroma intensity closest to the ideal was observed under conditions of low extrusion temperature and low moisture content of the raw material. © 2013 Elsevier Ltd.
Keywords: Corn grits; Flavor; Pre-flavored; Response surface methodology; Thermoplastic extrusion; Corn grit; Extrusion temperatures; Sensory acceptabilities; Structural characteristics; Volatile compounds; Flavors; Moisture determination; Screws; Volatile fatty acids; Volatile organic compounds; Extrusion; Zea mays